IMPORTANCE AND PERFORMANCE ANALYSIS OF WORKPLACE ENVIRONMENT IN GRAHA PENA (MANADO POST) - Tangkudung, Dion Berio; Worang, Frederik G.; Pandowo, Merinda . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Workplace environment is an important thing in organizations and give a big influence on employee?s performance. With a proper workplace environment like the facilities inside the office, employees are motivated and tend to improve the performance. This study came up in order to know how important workplace environment in Graha Pena and how is the performance of workplace environment in Graha Pena since those two factor are very important in terms of increasing or decreasing employees performance and comfort in working area. The study is using quantitative approach with Importance and Performance analysis with characteristic of respondent based on gender, age and educational background and the attributes are Indoor air quality, lighting, noise, furniture and tools and office environment. The result show lighting ,office environment and tools are the most important attribute in Graha Pena Manado post because they located at quadrant II which means it is in excellent level and quality even so, every aspect needs to be maintain in a good condition so that Graha Pena could be consistent in holding on to their success company. Keywords: workplace environment, indoor air quality, lighting, noise, furniture and tools, office environment, importance and performance analysis